Accurate Acetabular Component Positioning in Total Hip Arthroplasty Using Preoperative CT and Anatomical Landmarks - Min Uk Do; Kyeong Baek Kim; Sang-Min Lee; Hyun Tae Koo; Kuen Tak Suh; Won Chul Shin (Journal of Clinical Medicine, 2026)
Background: Accurate acetabular component anteversion during total hip arthroplasty (THA) remains challenging. We evaluated a preoperative computed tomography (CT)–based technique that uses patient-specific acetabular bony landmarks to position the cup. Methods: We prospectively enrolled 48 patients (50 hips) undergoing primary THA between September 2023 and January 2024. On preoperative CT, the anterior acetabular notch (AAN) was defined as the anterior pole, and the point opposite it across the acetabular center was defined as the posterior pole. Using the cup radius (r), the target-relative rotation (θ), and half the interpolar distance (R), the arc-length distances from each pole to the cup margin (a and b) were derived preoperatively with exact circular-geometry equations and reproduced intraoperatively. Postoperative CT anteversion was measured and converted to radiographic anteversion to determine outliers from the Lewinnek safe zone. Early clinical outcomes, including dislocation and modified Harris hip score (mHHS), were assessed at 3 months. Results: Mean postoperative CT anteversion was 25.1° (range, 16.0–35.0°), with a mean absolute error of 4.0° (range, 0–12.0°). Calculated radiographic anteversion was 16.8° (range, 10.0–24.0°), and all 50 hips were within the Lewinnek safe zone. At 3 months, mean mHHS was 92.4, and no dislocations were observed. Conclusions: This prospective proof-of-concept study suggests that CT-based acetabular bony landmarks can enable accurate cup positioning in standard primary THA. Further controlled studies are required to confirm reproducibility and clinical advantage.